Implementation of Mortgage Imposition by Land Deed Officials in Practice - Rehabeam Mofu (PT FORMOSA CENDEKIA GLOBAL, 2023)
Research on the Implementation of Mortgage Imposition by Land Deed Making Officials in practice was carried out to know the implementation of Mortgage Imposition made before the Land Deed Making Officer (PPAT) in practice and to find out the importance of clauses without prior approval from the Debtor (First Party) in the event of default in order to make a public sale by auction of the Mortgage object, either in whole or in part, following the applicable laws and regulations. The method used is a normative juridical approach. The study results the show that in practice, the Mortgage Granting Deed (APHT) is done, reads out, and then signed by the Giver and Mortgage Recipient in front of the Land Deed Making Officer (PPAT) in the presence of two witnesses. The importance of the clause without prior approval, regulated in the APHT format, is more to emphasize that the debtor giving the mortgage must complete his obligations according to the credit agreement. If a default occurs, the creditor can take an execution parate or executorial title to return the loaned capital to the debtor. Including the word for without prior approval is not by the agreed terms for the agreement's validity as stipulated in Article 1320 of the Civil Code. PPAT, in filling out the identity data of the Mortgage Giver, must be more careful in tracing the identity in the form of KTP and Family Card from the Mortgage Giver and need to revise the APHT editor, especially without prior approval from the debtor.